EXAMINING RESTORATIVE JUSTICE: DIFFERENT APPROACHES IN ISLAMIC CUSTOMARY LAW AND INTERNATIONAL PRACTICES - Sunbal Islam Chaudhary; Usman Asghar; Muhammad Afzal (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
Restorative justice is a conflict resolution technique that strives to give satisfactory victim resolutions, encourage offender accountability, and address the social impact, thereby overcoming the deficiencies of the traditional criminal justice system by bringing together all the parties involved. This paper explores the concept and alignment of restorative principles as a dispute resolution approach within both Islamic and customary law, with an emphasis on traditional dispute resolution methods such as mediation, arbitration, and conciliation. The paper emphasizes the significance of community involvement in conflict resolution and the compatibility of informal community processes with broader legal systems. This study also emphasizes the potential for cultural sensitivity and preservation of indigenous practices through the integration of restorative justice approaches in customary law systems. It specifically highlights the incorporation of restorative justice principles and ADR mechanism in Pakistan’s legal system and also focuses on the traditional dispute resolution practices such as jirga and panchayat in tribal areas of Pakistan. Through a thorough analysis of these ideas and procedures, this investigation aims to clarify the similarities, differences, and implementation of restorative justice strategies in these two unique legal frameworks. This study stresses the importance of restorative justice as a tool for promoting community healing and justice within Islamic and customary law followed by analysis and possible recommendations.